Madrasah Head's Strategy in Forming Students with Islamic Character through Superior Programs - Sugiono, Heru; Bisri, Abdul Mukti; Shonhadji; Khoiriyati, Salis (Journal of Education and Learning Innovation, 2024)
This research aims to: 1) To analyze the Islamic Character of Students MI AL KARIMAH Mojokerto City. 2) To analyze the Madrasah Principal's Strategy for Islamic Character Building at MI AL KARIMAH Mojokerto City.3) To find out the supporting and inhibiting factors faced in the implementation of the Flagship Program at MI AL KARIMAH Mojokerto City.The research method is descriptive qualitative with a case study approach. There are two types of secondary and primary data to support this research. Data collection techniques using observation, interviews and documentation. data analysis techniques using data collection, reduction, data presentation, and conclusion drawing. To test credibility in this study using triangulation. The results showed: 1) the Islamic character of students at MI Al Karimah is evident in the behavior of students, 2) The Principal's strategy in the formation of Islamic character in MI Al Karimah is planning, organizing, implementing, supervising and evaluating superior programs, namely: yaumiyah practice, reading and writing the Quran, Anjangsana and Muhadhoroh once a month. Supporting factors are: 1) Support from the school principal. 2) Cooperation of all teachers. 3) Support from parents of students. 4) School environment. The inhibiting factors in the formation of students with Islamic character are: parental supervision, children's socialization outside of school, lack of facilities and infrastructure in the form of school prayer rooms